Answer:
−(7p+6)−2(−1−2p) = - 3p - 4
Step-by-step explanation:
−(7p+6)−2(−1−2p) = -7p - 6 + 2 + 4p
= (-7p + 4p) + (2 - 6)
= -(7p - 4p) - (6 - 2)
= - 3p - 4
Answer:
738
Step-by-step explanation:
984 ÷ 100 = 9.84
9.84 × 75 = 738
75/100
Basically you’re multiplying them both
(x^3 + 2x - 1)(x^4 - x^3 + 3)
so you need to make sure you multiply each one, if you do it right, you should end up with
x^7 - x^6 + 3x^3 + 2x^5 - 2x^4 + 6x -x^4 +x^3 -3
simplify by adding like terms
x^7 - x^6 + 2x^5 - 3x^4 + 4x^3 + 6x - 3
your answer would be the third option
Answer:
D
Step-by-step explanation:
That is impossible but I did some math so there are 2 ways that will equal more than 40.
6.7×6.0=40.2
6.5×6.2=40.3
Hope this helps!